THE EFFECT OF USING VIDEO MEDIA ON STUDENT SKILLS IN PREGNANCY EXAMINATION PRACTICUM - Tri Wahyuni; Desy Syswianti; Andhika Lungguh Perceka (STIKes Karsa Husada Garut, 2023)
One of the competencies that must be mastered by midwives graduating from Diploma Midwifery is the skill to provide Antenatal Care (ANC) services, so prospective midwives are required to be truly skilled in pregnancy examination practicum. Midwife education institutions must have the right learning strategies and methods for pregnancy examination practicum, so that students can meet the competency standards of midwives. The purpose of this study was to determine the effect of using video media on student skills in pregnancy examination practicum. This study used a Quasi Experimental research design with Posttest-Only Control Group Design. The study population was 3rd semester students of D3 Midwifery Study Program at Karsa Husada College of Health Sciences Garut Academic Year 2022/2023. The sample consisted of 60 students who were divided into 2 groups, 30 respondents for the video group and 30 respondents for the demonstration group. The statistical test results showed a value of p less than 0.05. There is an effect of using video media on student skills in pregnancy examination practicum